Mathematics for pre-college students - Baranov, I.; Bogatyrev, G.; Bokovnev, O.; Levant, Leonid (trans.) ([S.l.] : Mir Publishers, 1985)
A study aid for students entering colleges, technical and vocational schools. The text consists of two parts: (1) arithmetic and algebra; and (2) geometry.